Relationship Knowledge and Personal Hygiene with Scabies Disease in Pesantren IMMIM Makassar: knowledge and personal hygiene with scabies - Sri ratna ningsih; Endang Sri Mulyawati L; Nur Juliana; Fatmawati M Saing (Politeknik Karya Persada Muna, 2021)
Background: Scabies is an infectious skin infection caused by the parasite Sarcoptes scabiei and the most common cause of lack of self-hygiene. Poor personal hygiene behavior is still a common factor in the transmission of scabies in santri caused by poor self-hygiene behavior and poorly maintained environment. This purpose to find out the relationship of knowledge and personal hygiene with the incidence of scabies in Pesantren IMMIM Putra Makassar Method: The study uses quantitative research methods with an observational analytic approach and uses cross-sectional study designs conducted in July-August 2021. Sampling technique uses purposive sampling with a sample number of 100 people. The instrument used is a questionnaire Results: The results showed that respondents who had experienced scabies with low knowledge were 15.5% and respondents with high knowledge experienced 34.5% scabies. The results of the statistical test obtained a p-value of 0.001 while that respondents who had experienced scabies with less personal hygiene were 31.5% and respondents who experienced enough scabies were 18.5%. The statistical test result obtained p-value is 0.534 Conclusions: The study concluded that there is a significant association between knowledge and the incidence of scabies disease while personal hygiene is not significantly related Keywords: Scabies, knowledge, Personal Hygiene